The perceived global manufacturing competitiveness of the South African autocatalytic converter industry - Keulder, Hendri (My University, 2014)
The South African autocatalytic converter has shown exponential growth during the last decade under the Motor Industry Development Plan (MIDP). Due to calls from the World Trade Organisation (WTO) for free and fair trade it was replaced with a different incentive programme called Automotive Production Development Programme (APDP) at the end of 2012. This research report aims to investigate the perceived competitiveness of the organisations within the South African autocatalytic converter industry and their readiness for the phasing out the MIDP programme after 2012. Firstly the perceived competitiveness of the industry was established through a comparative study of organisations within the industry and how they believe they compare to both international recognised operational best practises and their international competitors. The data for this study was gathered through structured interviews where the respondents were asked to subjectively compare themselves against their international competitors. Secondly a fuzzy cognitive map (FCM) was developed to determine the readiness of the industry for operating under the auspices of the APDP programme. This FCM was enhanced through interviews with industry leaders and finally used to simulate several plausible future scenarios to test the readiness of the industry to operate sustainably under APDP. This research report revealed that the industry considers itself to be either slightly behind or on the same level as their international competitors with regards to the various individual operational best practises considered in this study. The biggest challenge faced by the local industry is the big location disconnect of the industry to their primary markets in Western Europe and the associated additional transport costs. The simulations from the enhanced FCM revealed the sensitivity of the local autocatalytic converter industry to the global economic environment, external stimulus or support and particularly the economic health of the Western European countries.
MBA Thesis
Keywords: Motor industry -- South Africa.; Production management -- South Africa.